Validity and test–retest reliability of the Persian version of the Montgomery–Asberg Depression Rating Scale - Ahmadpanah M (Dove Medical Press, 2016)
Mohammad Ahmadpanah,1 Meisam Sheikhbabaei,1 Mohammad Haghighi,1 Fatemeh Roham,1 Leila Jahangard,1 Amineh Akhondi,2 Dena Sadeghi Bahmani,3 Hafez Bajoghli,4 Edith Holsboer-Trachsler,3 Serge Brand3,5 1Behavioral Disorders and Substances Abuse Research Center, Hamadan University of Medical Sciences, Hamadan, Iran; 2Hamadan Educational Organization, Ministry of Education, Hamadan, Iran; 3Center for Affective, Stress, and Sleep Disorders, Psychiatric Clinics of the University of Basel, Basel, Switzerland; 4Iranian National Center for Addiction Studies (INCAS), Tehran University of Medical Sciences, Tehran, Iran; 5Department of Sport, Exercise and Health Science, Sport Science Section, University of Basel, Basel, Switzerland Background and aims: The Montgomery–Asberg Depression Rating Scale (MADRS) is an expert’s rating tool to assess the severity and symptoms of depression. The aim of the present two studies was to validate the Persian version of the MADRS and determine its test–retest reliability in patients diagnosed with major depressive disorders (MDD). Methods: In study 1, the translated MADRS and the Hamilton Depression Rating Scale (HDRS) were applied to 210 patients diagnosed with MDD and 100 healthy adults. In study 2,200 patients diagnosed with MDD were assessed with the MADRS in face-to-face interviews. Thereafter, 100 patients were assessed 3–14 days later, again via face-to-face-interviews, while the other 100 patients were assessed 3–14 days later via a telephone interview. Results: Study 1: The MADRS and HDRS scores between patients with MDD and healthy controls differed significantly. Agreement between scoring of the MADRS and HDRS was high (r=0.95). Study 2: The intraclass correlation coefficient (test–retest reliability) was r=0.944 for the face-to-face interviews, and r=0.959 for the telephone interviews. Conclusion: The present data suggest that the Persian MADRS has high validity and excellent test–retest reliability over a time interval of 3–14 days, irrespective of whether the second assessment was carried out face-to-face or via a telephone interview. Keywords: major depressive disorders, Montgomery–Asberg Depression Rating Scale, validation, reliability